Smart Gardening: Simplified Seed Sowing Techniques - T.R. Vijayaram; Sundara Srinivasan; G. Nanthakumar; Naveen; C. Bhuvaneshwaran (International Journal of Machine Systems and Manufacturing Technology, 2024)
The primary objective of the exhibiting operation is to plant seed and fertilizer in rows at the proper depth and seed-to-seed spacing, cover the seeds with soil, and make sure there is enough compaction over the seed. To get the maximum yields, different recommended row-to-row spacing, seed rate, seed-to-seed spacing, and depth of seed placement are required for different agro-climatic conditions and crop kinds. A comparative analysis is conducted between the conventional sowing method and the newly suggested machine, which offers various advantages and can execute multiple tasks simultaneously. This machine lowers the effort and overall cost of seeding seeds and applying fertilizer, as labor availability and cost become increasingly of issues for farmers. The design and building of a semi-automated seed-planting device are covered in this study.
Keywords: Agro-climatic; Food demand; agricultural sector; seed-planting; weeding